Parallel Decentralized Network for the Detection of Unknown Signals Through Wireless Nakagami Fading Channels. (27th May 2010) - El-Bahaie, Ebtehal H.; Al-Hussaini, Emad K.
Abstract : In this paper analytical and simulation results for the decentralized detection of unknown signals are introduced. Parallel sensor network scheme is assumed. Additive White Gaussian Noise (AWGN) and Nakagami fading are assumed in both links, that is, from the source to the decentralized local sensors and from the sensors to the fusion center. Furthermore, diversity employing Square Law Combining (SLC) or Square Law Selection (SLS) is considered at each sensor, for both independent and correlated branches. Appreciable improvements are obtained with the increase of the number of sensors and the diversity employment.